Analysis of extracellular vesicle DNA at the single‐vesicle level by nano‐flow cytometry. Issue 4 (4th April 2022) - Liu, Haisheng; Tian, Ye; Xue, Chengfeng; Niu, Qian; Chen, Chen; Yan, Xiaomei
Abstract: It has been demonstrated recently that extracellular vesicles (EVs) carry DNA; however, many fundamental features of DNA in EVs (EV‐DNA) remain elusive. In this study, a laboratory‐built nano‐flow cytometer (nFCM) that can detect single EVs as small as 40 nm in diameter and single DNA fragments of 200 bp upon SYTO 16 staining was used to study EV‐DNA at the single‐vesicle level. Through simultaneous side‐scatter and fluorescence (FL) detection of single particles and with the combination of enzymatic treatment, present study revealed that: (1) naked DNA or DNA associated with non‐vesicular entities is abundantly presented in EV samples prepared from cell culture medium by ultracentrifugation; (2) the quantity of EV‐DNA in individual EVs exhibits large heterogeneity and the population of DNA positive (DNA + ) EVs varies from 30% to 80% depending on the cell type; (3) external EV‐DNA is mainly localized on relatively small size EVs (e.g. <100 nm for HCT‐15 cell line) and the secretion of external DNA + EVs can be significantly reduced by exosome secretion pathway inhibition; (4) internal EV‐DNA is mainly packaged inside the lumen of relatively large EVs (e.g. 80–200 nm for HCT‐15 cell line); (5) double‐stranded DNA (dsDNA) is the predominant form of both the external and internal EV‐DNA; (6) histones (H3) are not found in EVs, and EV‐DNA is not associated with histone proteins and (7) genotoxic drug induces an enhanced release of DNA + EVs, and the number of both external DNA + EVs and internal DNA + EVs as well as the DNA content in single EVs increase significantly. This study provides direct and conclusive experimental evidence for an in‐depth understanding of how DNA is associated with EVs.